ANALYSIS OF FINANCIAL DETERMINANTS OF URBAN COMMUNITY INTEREST IN HAJJ: STUDY OF THE BUGIS TRIBE IN MAKASSAR AND MANADO - Ridwan Tabe; Satriani Satriani; Telsy Fratama Dewi Samad; Suci Indriani Sarka (Akademika : Jurnal Pemikiran Islam, 2023)
The urge of the Bugis community to carry out the Hajj pilgrimage is increasing, particularly in the cities of Makassar and Manado. This is because in urban areas the Hajj pilgrimage is a cultural priority for the community. The ability to carry out the Hajj pilgrimage is measured by financial determinants including asset value, savings investment, income level, and religious understanding. This research is intended to analyze the influence of asset value, savings investment, and income level on interest in Hajj by involving religiosity as a mediating variable in the Bugis community in the cities of Makassar and Manado. This research followed a quantitative approach by collecting data through questionnaires. The population in this study was the entire Bugis community who are living in Makassar and Manado, while the sample was taken according to the sample selection criteria of 607 respondents. The data analysis technique used is path analysis with the help of AMOS (Analysis of Moment Structure) software. The results of this research show that the value of assets does not have an influence on the interest in Hajj of the Bugis community in Makassar and Manado, however, the value of assets and investment savings has an influence on the interest in Hajj of the Bugis community if the religiosity variable is involved as a mediating variable, while the level of income has no influence on interest in Hajj by the Bugis community in Makassar and Manado. The novelty of this research is connecting multiple variables with the Hajj interest variable using the religiosity variable as a moderating variable by creating a new pattern by testing competitive theory. The implication of this research is the increase in the number of registrants or Hajj portion numbers because it is supported by investment savings available from banking products.